PARETO DIAGRAMS STUDY OF GROSS REGIONAL DOMESTIC PRODUCT EXPOSURE IN CERTAIN SECTORS IN A REGION - Ceni Febi Kurnia Sari; Supardi (JURUTERA - Jurnal Umum Teknik Terapan, 2022)
Study is learning scientific study. A Pareto chart is a diagram consisting of a bar graph and a line graph that illustrates a comparison of each type of problem data with its overall causes. Gross Regional Domestic Product (PDRB) is the total gross added value arising from all economic sectors in a particular area. Which is usually a Pareto Diagram made to describe the PDRB of a particular area which aims to help make regional policies or planning, evaluate development results, provide information that can describe the regional economic performance. In terms of the topic of this pareto diagram study, the author takes the exposure of rock mining in Manokwari Regency. The mining of these rocks is a source of income in the Manokwari Regency area which can support the economy in the Manokwari Regency area. Where mining activity or mining activity is a process or activity of taking material that can be extracted from the earth to the utilization of minerals, both for the benefit of the company, the surrounding community, as well as local and central government.